Anopheles parensis contributes to residual malaria transmission in South Africa - Ashley Burke; Yael Dahan-Moss; Frances Duncan; Bheki Qwabe; Maureen Coetzee; Lizette Koekemoer; Basil Brooke (Malaria Journal, 2019)
Abstract Background Understanding the contribution of outdoor-resting Anopheles mosquitoes to residual malaria transmission is important in terms of scaling up vector control towards malaria elimination in South Africa. The aim of this project was to assess the potential role of Anopheles parensis and other Anopheles species in residual malaria transmission, using sentinel surveillance sites in the uMkhanyakude District of northern KwaZulu-Natal Province. Methods Monthly vector surveillance was conducted at the sentinel sites from January 2017 to May 2018. Outdoor-placed clay pot resting traps were used to collect male and female adult Anopheles mosquitoes. All Anopheles gambiae complex and Anopheles funestus group specimens collected were identified to species and all females were screened for Plasmodium falciparum circumsporozoite protein (CSP) by enzyme-linked immunosorbent assay (ELISA). Samples showing infectivity for P. falciparum were further verified by a nested PCR and subsequent DNA sequence analysis. Results From a sample of 491 anophelines, Anopheles arabiensis (n = 228) and An. parensis (n = 194) were the most abundant. Other species collected included Anopheles merus (n =11), Anopheles quadriannulatus (n = 10), Anopheles leesoni (n = 29), Anopheles rivulorum (n =18), and Anopheles vaneedeni (n =1). Of the 317 female specimens screened for P. falciparum CSP, one Anopheles arabiensis and one An. parensis showed positive by ELISA and Plasmodium nested PCR. For the An. parensis specimen, confirmation of its species identity was based on sequence analysis of the ITS2 region, and the presence of P. falciparum DNA was further confirmed by sequence analysis. Conclusions Anopheles parensis is a potential vector of malaria in South Africa although its contribution to transmission is likely to be minimal at best owing to its strong zoophilic tendency. By contrast, An. arabiensis is a major vector that is primarily responsible for the bulk of residual malaria transmission in South Africa. As all recently collected sporozoite-positive Anopheles mosquitoes were found in outdoor-placed resting traps, it is necessary to introduce interventions that can be used to control outdoor-resting vector populations while maintaining the efficacy of South Africa’s indoor house spraying operations.